The Consequences of Knowledge about Elite Deviance - Michel, Cedric (American journal of criminal justice, 2016)
The present study sought to understand the consequences of knowledge about elite deviance. Four hundred and eight participants completed an online questionnaire that measured (1) their level of knowledge about white-collar crime and (2) their perceived seriousness of, and punitiveness toward, it. Results of statistical analyses suggest a positive relationship between knowledge and punitive sentiments toward crimes of the powerful. Conversely, less knowledgeable subjects, comprised disproportionately of men, politically Conservatives, Republicans, and conservative Protestants were often more lenient toward elite offenders, both in terms of perceived seriousness of the offenses and punitiveness toward them, when compared with street crime. Implications of these findings are discussed.